Investigating TSHR gene variants in consanguineous families: novel insights into variable expression in familial congenital hypothyroidism - Nadeali, Zakiye; Mohammadi-Zaniani, Zohreh; Biglari, Sajjad; Molavi, Newsha; Zardoui, Khashayar; Mirfendereski, Sam; Hashemipour, Mahin; Tabatabaiefar, Mohammad Amin; Polychronakos, Constantin (Frontiers in Endocrinology, 2025)
BackgroundA defective thyroid-stimulating hormone receptor (TSHR) gene is one of the main known genetic factors leading to congenital hypothyroidism (CH). However, the relationship between TSHR genotypes and phenotype and the underlying reason for the broad spectrum of phenotypes in the patients carrying TSHR gene defects have not yet been clearly established. This study aimed to investigate the genetics of patients with CH to identify TSHR defects and to explore the specific extrathyroidal defects and other phenotypic features in these patients to establish a genotype-phenotype correlation.MethodsConsanguineous families with primary CH and a history of non-autoimmune acquired hypothyroidism were included in this study. The causative variants in the TSHR gene were identified using exome sequencing. Multiple in silico analysis tools were employed to interpret the variants.ResultsFive TSHR variants including two novel variants were identified in patients with thyroid dysgenesis from five families. Some patients presented inter- and intra-familial variable expression and different ages of onset. The data suggest the possibility that the clinical phenotype of patients with CH caused by TSHR variants can be influenced by the coexistence of other gene defects.ConclusionsThis study investigated the variants of the TSHR gene contributing to CH for the first time in Iran. Our study on multiplex consanguineous families could help provide further evidence for the elucidation of the oligogenic inheritance in CH, possibly leading to variable expressivity in patients with CH. These data could have implications for genetic diagnosis and counseling to identify deleterious variants for possible diagnostics, clinical management, and preventive aims.